Assessment of asthma control using CARAT in patients with and without Allergic Rhinitis: A pilot study in primary care. - Domingos, M; Amaral, R; Fonseca, JA; Azevedo, P; Correia-de-Sousa, J (My University, 2016)
BACKGROUND: Asthma and Allergic Rhinitis (AR) are two chronic inflammatory diseases that are often concomitant. The Control of Allergic Rhinitis and Asthma Test (CARAT) was developed to evaluate the control of these diseases from the patients' perspective. Its performance in asthma patients without AR has not been previously studied. AIM: To test the hypothesis that CARAT can be used to assess asthma control in patients with asthma and without AR. METHODS: A cross-sectional study was conducted in 3 primary healthcare centres in Northern Portugal. Adult patients identified in the Electronic Patient Record with a diagnosis of asthma were invited to participate. CARAT was used to assess asthma control and Asthma Control Test (ACT) as a comparator. The associations between asthma patients without AR (AsAR) and with AR (AwAR) were analyzed with Spearman correlation. Additionally, Receiver Operating Characteristic (ROC) curve analysis, summarized by Area Under the Curve (AUC), was used to assess performance of CARAT for screening asthma that was not well-controlled. RESULTS: A total of 103 asthma patients completed the study, 64 (62%) had AwAR and in 87 (85%) asthma was not well-controlled. We observed a strong correlation between CARAT and ACT scores (r=0.734) in all asthma patients and in both groups: AsAR (r=0.737) and AwAR (r=0.843). ROC curve demonstrated CARAT as having a good discriminative power for both AsAR and AwAR groups (AUC=0.894 and 0.946, respectively). CONCLUSION: These initial results suggest that CARAT has a good discriminative performance, similar to other asthma control assessment tools, for asthma patients with and without AR.
Keywords: Asma; Rinite Alérgica; Asthma; Rhinitis, Allergic